Interspecific hybridization of Centrosema pubescens WITH Centrosema virginianum - Serpa, Aryno (Pesquisa Agropecuaria Brasileira, 2014)
Studies carried out in Itaguaí, Rio de Janeiro, which took place in the Instituto de Pesquisa Agropecuária do Centro-Sul (IPEACS) yielded interspecific hybrids of Centrosema pubescens with Centrosema virginianum and also the reciprocal hybridization. It was observed that the main characteristics under selection such as initial growth rate, nitrogen fixation, rooting ability, vegetative development and good seed production are present in the F1 generation as dominant traits. Objectives were established on the genetic improvement of Centrosema incorporating the above characteristics in order to select a cultivar of higher productivity.